2022
DOI: 10.3389/fphar.2022.845615
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Recanalization of Branch Retinal Artery Occlusion Due to Microthrombi Following the First Dose of SARS-CoV-2 mRNA Vaccination

Abstract: Background: We report on a patient with a branch retinal artery occlusion (RAO) and its recanalization based on multimodal retinal and angiographic images after he was administered the first dose of the SARS-CoV-2 mRNA vaccine.Case summary: A 64-year-old man complained of a right, painless, inferior field defect 3 days after the first dose of BNT162b2 vaccination. Fundus examination revealed decolorization of the right upper macula, including microthrombi in the superior proximal branch of the retinal artery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…ACVS and PACVS) have been published yet but corresponding observations have already been made during medical examinations (Beate R. Jaeger, personal communication). Microthrombi were detected in biopsies of tissue in case of COVID-19 [390] , [391] , [392] , [393] and PCVS (in general in the case of VITT) [394] , [395] , [396] , [397] , [398] , [399] , [400] , [401] , [402] .
Fig.
…”
Section: Sars-cov-2 Infection- and Covid-19 Vaccination-induced Syndr...mentioning
confidence: 99%
“…ACVS and PACVS) have been published yet but corresponding observations have already been made during medical examinations (Beate R. Jaeger, personal communication). Microthrombi were detected in biopsies of tissue in case of COVID-19 [390] , [391] , [392] , [393] and PCVS (in general in the case of VITT) [394] , [395] , [396] , [397] , [398] , [399] , [400] , [401] , [402] .
Fig.
…”
Section: Sars-cov-2 Infection- and Covid-19 Vaccination-induced Syndr...mentioning
confidence: 99%
“…Two patients with retinal ischemic events after application of the Moderna vaccine (MOV) respectively the Johnson & Johnson vaccine (JJV) have been recently reported 6 . Kang et al reported a 64yo male who experienced a branch retinal artery occlusion three days after the first dose of the Biontech Pfizer vaccine (BPV) 7 . A 76yo female developed unilateral, painless visual loss 2 days after the first dose of the AZV 8 .…”
mentioning
confidence: 99%
“…The interval was 1 day for one patient diagnosed with branch retinal arterial occlusion, and shorter than 1 day for two patients diagnosed with central retinal arterial occlusion and vitreous hemorrhage, respectively. Retinal arterial occlusion has been previously reported after vaccination with the mRNA COVID-19 vaccine, and were characterized by non-embolic, not accompanied by carotid plague or stenosis, rapid development within 2 weeks after vaccination, and without marked abnormalities of laboratory tests (such as increased D-dimer and C-reactive protein) [7]. The mean age of patients diagnosed with retinal vascular occlusion in the present study was 53 years, which was comparable to that of patients diagnosed with retinal vascular occlusion not associated with vaccination (53 years old) [25].…”
Section: Discussionmentioning
confidence: 87%
“…Inactivated COVID-19 vaccines have been widely used among the Chinese population and have shown good safety, tolerability, and immunogenicity [3,4]. Nevertheless, ocular adverse events have rarely been reported after COVID-19 mRNA vaccines, vector vaccines, and inactivated vaccines [5][6][7]. A relationship has not be established between reported ocular disorders and COVID-19 vaccines, because of limited awareness of the clinical spectrum of potential ocular adverse events, and unclear mechanisms for ocular disorders and COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%